The Main Compounds and Major Methods in Latent Fingermark Aging Analysis: a Short Review - Marina González; Roberta Petry Gorziza; Danielle Kochenborger John; Jonathaline Apollo Duarte; Renata Pereira Limberger; Marco Flôres Ferrão; Kristiane de Cássia Mariotti; Andreas Sebastian Loureiro Mendez (Drug Analytical Research, 2023)
Fingermarks are a complex biological matrix with variability factors that change in the same donor, depending on the moment of collection, and in different donors, according to age, sex and routine. Thus, they can still undergo alterations related to the deposition surface, the environment, and the variable that connects all those mentioned: the action of time. In Forensic Science, time is a important variable to situate the crime events. This review proposes a classification in the temporal estimation research of fingermarks, dividing them into Temporal Preservation Analysis (TPA) and Temporal Aging Analysis (TAA). In TPA studies, the components in fingermark residues undergo a few changes over time, tending to stability after a certain period. Those are interesting targets to identify possible exogenous components, such as firearm residues, illegal substances and contaminants related to particularity of forensic cases. In TAA studies, a time estimation related to the fingermarks age can be established. In this case, the time elapsed from its deposition until the forensic processing will vary according to the component classes degradation. Endogenous and exogenous substances that are demonstrably present in one donor and that undergo changes over time will, resulting be demonstrated by a decrease in intensity and/or formation of other substances, and those are good targets for this type of study. The same analysis can have both proposals and the instrumental method available will enable the extraction of information relevant to the sample. The purpose of this study is to demonstrate how important is to identify fingermarks components as evidence beyond the ridge pattern and to list the main instrumental methods used in the analysis of fingermark degradation.